Short Communication: Temporal and spatial variations of Rhodophyta communities along the Chabahar Coast, Oman Sea - ABEDEH JAMSHIDZEHI; NEDA MEHDIPOUR; NASER JAFARI; MAHMOUDREZA AZINI (Society for Indonesian Biodiversity, 2017)
Jamshidzehi A, Mehdipour N, Jafari N, Azini M. 2017. Short Communication: Temporal and spatial variations of Rhodophyta communities along the Chabahar Coast, Oman Sea. Biodiversitas 18: 619-622. Monthly sampling of macroalgae was carried out from January 2014 to November 2014 in Iranian Coasts of Oman Sea along Sistan and Baluchistan province coastal waters. Monthly sampling was done by a number of transects with equal distance and in randomly chosen 50Ã—50cm quadrates. The samples were transferred to the lab and after cleaning and separating, identified up to species level. A total of 17 species of Rhodophyta were recognized, and the most observed families included: Gelidiaceae, Gracilariaceae, Hypneaceae and Rhodomelaceae. The maximum algal biomass and of species belonged to Gracilaria corticata. Laurencia obtusa, Hypnea valentiae and Gracilaria corticata observed in all stations and seasons. Laurencia obtusa, Hypnea valentiae and Gracilaria corticata observed in all stations and seasons. Comparing to the previous study in the Chabahar Coast, steep decline in the number of observed macroalgae species in this region was observed.